Creating historical clothes : pattern cutting from Tudor to Victorian times - Friendship, Elizabeth (Batsford, 2013)
This stunning collection of period garments spans 400 years of fashion, from 1550 to 1900. Draft your own made-to-measure patterns to create perfectly fitted bodices, sleeves, skirts, trousers and much more. This unique method of pattern cutting ensures that, regardless of differences between the historical garment and the modern wearer, the clothes will fit all shapes and sizes perfectly, and patterns can be drafted from illustrations or paintings where no original exists. Easy-to-follow instructions for adapting the basic patterns enable the cutter to recreate any historical style, while simple illustrations and diagrams demonstrate how to emphasize the period elements and achieve the correct shapes. Lavishly illustrated with historical paintings and portraits, this practical book will both guide and inspire the reader throughout.